Coordination incentives in cross-border macroprudential regulation - Alexis Derviz; Jakub Seidler (Charles University in Prague, Institute of Economic Studies (IES), 2012)
We discuss (dis)incentives for fair cooperation related to delegating macroprudential policy decisions to a supranational body, as well as their welfare implications. The question is studied by means of a signaling game of imperfect information between two national regulators. The model concentrates on informational frictions in an environment with otherwise fully aligned preferences. We show that even in the absence of evident conflicting goals, the non-transferrable nature of some regulatory information creates misreporting incentives. However, the major problem is not the reporting accuracy but the institutional arrangement focused on maximal multilateral satisfaction to the detriment of credible enforcement of rules. The main application is meant to be systemic risk management by the relevant EU institutions.
Keywords: F55; H77; D02; C72; D83; 330; macroprudential regulation; integration; autonomy; information; reporting; Bankenaufsicht; Regulierung; Unvollkommene Information; Signalling; Spieltheorie